PENGARUH KINERJA DAN RISIKO REKSADANA TERHADAP JUMLAH ASSET UNDER MANAJEMEN DAN UNIT PENYERTAAN - ISNURHADI . (Program Studi Magister Manajemen FE Unsri, 2014)
The aim of this study was to conduct an analysis of the performance of stock mutual funds in Indonesia as well as to assess whether there is influence between the performance of mutual funds with AUM change and IU of mutual funds. Analysis of the performance of mutual funds is done by using Sharpe's Ratio. The performance is then compared to its benchmark which JCI and EFI . Furthermore, the authors use regression analysis to derive the relationship between the independent and dependent variables as well as the use of risk as a moderator variable.The results showed only 3 stock mutual fund products that is able to beat the performance of JCI and 9 stock mutual fund products are capable of beating EFI as a benchmark. Meanwhile there are significant between the performance (Sharpe 's Ratio), Risk, AUM1) and IU but not so significant. This shows there are other contributing variables outside the model study that affect the relationship. Assets Under Management; Investment Units; Composite Stock Price Index; Equity Index Fund